2022
DOI: 10.1098/rspa.2022.0294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stacking order on the vibration properties of bilayer black phosphorus

Abstract: The effect of the stacking order of bilayer black phosphorus (BLBP) on the vibration properties is investigated by using molecular dynamics (MD) simulation and continuum modelling. The results show that the interlayer shear effect plays a very important role in the vibration behaviours of BLBPs. In MD simulation, a negative shear modulus is found in BLBP nanoresonators with stacking orders AA and AA′, which can decrease the natural frequency of the nanoresonators. The prediction of the natural frequency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Zhang et al [12] modelled an orthotropic plate model to investigate on the linear vibration of black phosphorus. Zhang et al [13,14] conducted a study on the vibration of circular double-layered black phosphorus and double-layered MoS 2 considering the interlayer shear effect. They found that the stack order can affect the natural frequency significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [12] modelled an orthotropic plate model to investigate on the linear vibration of black phosphorus. Zhang et al [13,14] conducted a study on the vibration of circular double-layered black phosphorus and double-layered MoS 2 considering the interlayer shear effect. They found that the stack order can affect the natural frequency significantly.…”
Section: Introductionmentioning
confidence: 99%